Analysis of the Causes of Reading Difficulties In Class V Students of SDN 3 Sukamanah - Rahmayanti, Putri; Rakhmat, Cece; Chandra, Deni (Zona Education Indonesia, 2024)
Many factors cause the low level of literacy among Indonesian society, namely (1) internal factors (2) external factors. Based on the results of research observations at SDN 3 Sukamanah which is in Cisingkah hamlet, Sukamanah village, Sindangkasih sub-district, Ciamis district, there are problems that indicate there are students who cannot read, one of which is class V, with 5 students declared unable to read. This situation shows that there are factors that cause reading difficulties in students. So the aim of this research is to analyze reading difficulties in class V students at SDN 3 Sukamanah. This research method uses qualitative descriptive research. In this research, the data collection techniques used by researchers are tests, observations, interviews. Based on the results of observations and interviews conducted by researchers regarding children who have difficulty reading, researchers analyzed 3 aspects of reading word order, understanding sentences, and paying attention to punctuation. There are 2 factors that can cause children not to be able to read, namely internal factors and external factors. .2 out of 5 students studied, namely JCM and MMF, experienced intellectual factors. FMS, HAM, JCM, MMF, and RPP also experience internal factors, namely psychological factors, then 3 out of 5 students, namely, FMS, JCAM, MMF, have inhibiting factors from the family